Karfule - Ghosh, Ayan (2023)
The vertical accent provided by the tower at Karfule is distinctly Art Deco. The tower originally served as a clock tower. The clock was replaced by the Caltex sign, and since 1978, the Hindustan Petroleum logo. The Caltex sign remains with the Sequeira family as part of the pump's historical archive of objects.